2018
DOI: 10.1016/j.ajpath.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts Promote Inflammation and Pain via IL-1α Induction of the Monocyte Chemoattractant Chemokine (C-C Motif) Ligand 2

Abstract: Fibroblasts persist within fibrotic scar tissue and exhibit considerable phenotypic and functional plasticity. Herein, we hypothesized that scar-associated fibroblasts may be a source of stress-induced inflammatory exacerbations and pain. To test this idea, we used a human model of surgery-induced fibrosis, total knee arthroplasty (TKA). Using a combination of tissue protein expression profiling and bioinformatics, we discovered that many months after TKA, the fibrotic joint exists in a state of unresolved chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
0
29
1
Order By: Relevance
“…Inflammation, fibrosis, and pain are dependent on immune cell recruitment and activation. We have previously found infiltration of CD68 + monocytes into fibrotic tissue . Therefore, we first examined GM‐CSF (increased ~threefold in SF of revision versus primary knees), IL‐5 (increased sixfold), IL‐8 (increased 39‐fold), and IL‐10 (increased twofold).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…Inflammation, fibrosis, and pain are dependent on immune cell recruitment and activation. We have previously found infiltration of CD68 + monocytes into fibrotic tissue . Therefore, we first examined GM‐CSF (increased ~threefold in SF of revision versus primary knees), IL‐5 (increased sixfold), IL‐8 (increased 39‐fold), and IL‐10 (increased twofold).…”
Section: Resultscontrasting
confidence: 59%
“…Data presented in this report suggest that the levels of key biologically active pro‐inflammatory mediators are locally elevated at time of revision surgery many years after the initial procedure in failed TKAs. The painful, fibrotic post‐TKA joint acquires a state of unresolved inflammation with a signature resembling that of a chronic allergic reaction . Markers with this temporal regulation include those involved in matrix formation (VEGF, Flt‐1) and the inflammatory cytokines GM‐CSF, IL‐5 and IL‐8, and cell recruitment chemokines CCL2, CCL3 and CCL4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximated five percent of patients suffer stiffness as a significant complication after their TKA [6], and some require manipulation under anaesthesia [22] or revision surgery because of persistent stiffness [18]. Stiffness after knee arthroplasty may have a genetic component and epidemiological studies have found chromosomal changes in those reporting such symptoms [14], with an increased understanding of the biological basis for such a host response [16]. This is leading to a greater awareness that stiffness is potentially avoidable both from a mechanical and biological perspective [6].…”
Section: Introductionmentioning
confidence: 99%